GAMBARAN KARAKTERISTIK KEJADIAN IKUTAN PASCA VAKSINASI COVID-19 PADA TENAGA KESEHATAN ALUMNI UNIVERSITAS ‘AISYIYAH SURAKARTA - Lidiana, Exda Hanung; Mustikasari, Hanif; Pradana, Krisnanda Aditya; Permatasari, Andria (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
Purposes: Knowing the description of the characteristics of Post-Vaccination follow-up events in health workers who are A Graduate 'Aisyiyah University Surakarta who received Covid -19 vaccination. Methods: The research design was a descriptive study with a cross-sectional method. The research subjects were 95 alumni of 'Aisyiyah University Surakarta, graduates from 2010-2020 who had received the covid-19 vaccine. This research was conducted virtually through the google-form application by respondents in their respective work areas. This research was conducted in March 2021. The data collection technique used in this study was purposive sampling Results: Characteristics of the age of the majority of respondents based on age were 20-30 years old as many as 75 respondents (78.9%), Gender characteristics of the majority of respondents based on gender were women as many as 85 respondents (89.5%). profession is a nurse as many as 63 respondents (66.3%), Characteristics of previous medical history of the majority of respondents based on past medical history are 86 respondents (90.5%), the characteristics of the occurrence of AEFI events, the majority of respondents are based on the incidence of AEFI after vaccine As many as 85 respondents (89.5%) did not have Covid-19, the characteristics of the types of AEFI symptoms were the majority of respondents based on the incidence of AEFI after the Covid-19 vaccine appeared fever was no fever as many as 85 respondents (89.5%), the majority of respondents were based on incidence. AEFI after the Covid-19 vaccine appeared diarrhea was no diarrhea as many as 93 respondents (97, 9%), the majority of respondents based on the AEFI incidence after the Covid-19 vaccine appeared coughing was no cough as many as 93 respondents (97.9%), the majority of respondents based on the AEFI incident after the Covid-19 vaccine appeared shortness of breath was no shortness of breath as many as 93 of respondents (97.9%), the characteristics of the duration of AEFI symptoms, the majority of respondents, based on the duration of the occurrence of the event, were absent (for those without symptoms) as many as 84 respondents (88.4%). Conclusion: The characteristics of the emergence of AEFI in respondents who received Covid-19 vaccination based on age, sex, profession, past medical history, number of AEFI incidents, types of AEFI symptoms, and duration of AEFI symptoms appeared were minimal.